INTERPRETASI STRUKTUR BAWAH PERMUKAAN BERDASARKAN DATA GEOMAGNETIK PADA DAERAH MATA AIR PANAS JATIKURUNG KABUPATEN SEMARANG - Laela Fitria; Tony Yulianto; Udi Harmoko (Youngster Physics Journal, 2015)
The interpretation of subsurface structure and the identification of caused of the hot springs Jatikurung by using magnetic method have been successfully carried out. In this study, magnetic data acquisition was carried out in 71 points by using a PPM (Proton Precession Magnetometer) geometrics type of GSM 19T models to get the values of the total magnetic field. Data processing began with IGRF (International Geomagnetic Reference Field) correction and diurnal correction to get the total magnetic anomaly. The corrected data has been used to create total magnetic anomaly contour. The total magnetic anomaly contour has been used to process reduction to plan surface. The result of reduction to plan surface has been used to create a contour upward continuation and then made reduction to the poles. The result of research showed the total magnetic anomaly closure pair of positive and negative indicated a fault zone below the surface. The closure pair of positive and negative close to the manifestation was made an incision to determine the subsurface structure of the region by creating a model of 2-dimensional (2D) using software Mag2DC. In 2D modeling result show that there was a fault zone about 1200 meters depth. At a depth of 326 to 1200 meters was interpreted as a cap rock with a value 0.2926 (SI). The exhibition of the hot springs Jatikurung was interpreted by the finding of adjacent fault with igneous intrusion which was estimated to save the residual of magma that can be used as a heat source.